Jabatan Kerja Raya, Jalan Osman, Muar / Khabir Nabil Mohd Sa'id - Mohd Sa'id, Khabir Nabil (UiTM Johor Cawangan Kampus Pasir Gudang, 2018)
This report is about my industrial training that I have gone through for a total of 8 weeks from the 8" of July until 2°4 of September 2018. I was placed at Muar Public Works Department or commonly known as Jabatan Kerja Raya (JKR) Muar. The main reason I chose this place to accomplish my training is because I would like to gain knowledge and experience in the government sector as my family career history is mostly in the private sector. The location of training is not too far away from my -house as well. The internship has provided me with great experiences to learn and improve and also develop new set of skills. Moreover, the experienced gained-at PWD Muar has taught me about the work conditions of an organization.